Pengaruh Model Creative Problem Solving (CPS) Berbantuan Gamifikasi Wordwall terhadap Kemampuan Pemecahan Masalah Matematis Siswa pada Materi SPLD - Siti Nurul Qomariyah; Supardi Supardi (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
The study examines the effects of implementing the Creative Problem Solving (cps) instructional model integrated with Wordwall gamification on the mathematical problem solving abilities of eighth-grade Students at MTs. L-Bashriyah. The purpose of this research is to avaluate the impact of CPS combined with Wordwall on students’ Performance in Two-Variable Linear Equation Systems (SPLDV) compared to conventional methods. This research employs a Quasi-Experimental design with a non-equivalent pretest-posttest control group. Using a quantitave approach. The sample consists of 40 eighth-grade students of MTs. AL-Bashriyah as the experimental group and 32 students of MTs. Nurul Huda as the control group. Selected through purposive sampling. Data analysis utilizes normalized gain scores and descriptive statistics with a 5% significance threshold. Results indicate a statistically significant improvement : the experimental group’s average postest score (81.16) markedly increased from the pretest (33.99). The control group showed moderate growth (66.45 from 32.91). Normalized gain analysis classifies the experimental group’s progress as high and the control group’s as medium. The findings demonstrate that CPS-Wordwall integration significantly enhances mathematical problem-solving skills. Thus, this model presents a viable innovative strategy for SPLDV instruction.